2012
DOI: 10.1136/sextrans-2011-050348
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal syndrome secondary toPrevotella biviaafter accidental bite in orogenital sex

Abstract: The authors report a case of an inguinal bubo in a young man caused by an anaerobe, Prevotella bivia, which was acquired during oral sexual intercourse. As far as the authors know, this is the first reported case of a sexually transmitted infection by Prevotella. Prevotella spp. inhabit the oral cavity and are highly prevalent in bacterial vaginosis, a polymicrobial syndrome resulting from replacement of the normal vaginal Lactobacillus spp. flora by high concentrations of anaerobic microorganisms such as Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Table 2 summarizes previous reports of Prevotella bivia infections as published in PubMed. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Similar to our case, the case presented by Bekasiak et al involved a scrotal abscess and co-infection with a second bacterial genus. 11 Additionally, co-infection occurred in 7 cases, including 2 cases with Prevotella bivia and Streptococcus anginosus, a well-known species that produces an abscess.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 2 summarizes previous reports of Prevotella bivia infections as published in PubMed. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Similar to our case, the case presented by Bekasiak et al involved a scrotal abscess and co-infection with a second bacterial genus. 11 Additionally, co-infection occurred in 7 cases, including 2 cases with Prevotella bivia and Streptococcus anginosus, a well-known species that produces an abscess.…”
Section: Discussionsupporting
confidence: 89%
“…5 Prevotella bivia infections in humans are rare, with only 18 published cases in 44 years. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Since most Prevotella bivia strains are β-lactamase-positive, 24 clindamycin, amoxicillin/clavulanate, metronidazole, and imipenem are the recommended antibacterial agents. 21,25 However, antibiotic resistance varies across countries, 26 and it is unknown whether Prevotella bivia strains in Japan are β-lactamase positive.…”
Section: Introductionmentioning
confidence: 99%
“…Prevotella species are anaerobic commensals of the mouth and could contribute to oral inflammatory processes [ 4 ]. Rarely, they can cause cervicofacial infections [ 6 , 7 ], peritoneal and pelvic cavity infections ( P. bivia and P. disiens ) [ 8 ], surgical or human bite wound infections [ 9 ], and hepatosplenic abscesses [ 10 ]. Cases of NF caused by Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Male genitourinary tract has also been reportedly affected; Nalmas et al [8) reported P. bivia causing a penile abscess requiring surgical drainage. Sagristà et al [9] described a case of inguinal bubo in a young male acquired as part of sexually transmitted infection. Other rare case reports secondary to P. bivia include Necrotising Fasciitis [10], abdominal wall phlebitis following renal transplantation and inferior vena cava obstruction [11], chest wall abscess [12], and P. bivia associated Lemierre Syndrome [13].…”
Section: Discussionmentioning
confidence: 99%